The identification of technical specifications of competency curriculum printing for the second grade in the State of Kuwait with the international standards from science teachers Perspective - Althafeeri, Bushra Habbad (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the conformity of the technical specifications in printing the competency curriculum for the second grade of primary school in the State of Kuwait with international standards from the point of view of science teachers. The researcher used the descriptive analytical approach. A questionnaire was used as study instrument. The study used a random sample consisted of 62 female teachers from Al Farwanieh area. The study concluded that the reseah instrument mean was (3.65) for the conformity. As for research dimensions the general form and artistic dimension quality mean was (3.97) with high rating, while technical adjustment of colors, graphics, maps, and photos dimension mean was (3.58) with medium rating. With respect to specifications and conditions for typographical and artistic coordination dimension mean was (3.40) with medium rating. Finally, documentation and references conformity mean was (3.50) with medium rating Based on, the researcher recommended the necessity of paying attention to printing and technical coordination and designing books in accordance with the size and weight of the book and the age stages of the students, and paying attention to the formation of the book sufficiently according to the established level and in an ideal form. Conducting more studies on the specifications and technical conditions for printing the curricula and the extent of their application by the Curriculum Development Department in the State of Kuwait, and comparing their results with the results of the current study.